2013
DOI: 10.1111/jch.12104
|View full text |Cite
|
Sign up to set email alerts
|

Association of B2 Receptor Polymorphisms and ACE Activity With ACE Inhibitor–Induced Angioedema in Black and Mixed‐Race South Africans

Abstract: 4Angiotensin-converting enzyme (ACE) inhibitors are first-line therapy for the treatment of hypertension, congestive heart failure, and diabetic nephropathy. ACE inhibitors are associated with adverse side effects such as persistent dry cough (ACE-cough) and, rarely, life-threatening angioedema (ACE-AE). The authors investigated the influence of ACE I/D polymorphism in combination with serum ACE activity, B 2 receptor À9/+9 polymorphism, and B 2 receptor C-58T single nucleotide polymorphism (SNP) on the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…109 However, three further case-control studies did not support these initial findings. [96][97][98] One of these studies reported a 50% lower ACE activity in ACEi-A cases compared to controls taking the same drug, and independent of the presence of the insertion/deletion variation 98 and, the two other studies failed to replicate this finding. 96,97 No other variants in ACE gene have been studied in association with ACE-A.…”
Section: Ace Genementioning
confidence: 99%
See 3 more Smart Citations
“…109 However, three further case-control studies did not support these initial findings. [96][97][98] One of these studies reported a 50% lower ACE activity in ACEi-A cases compared to controls taking the same drug, and independent of the presence of the insertion/deletion variation 98 and, the two other studies failed to replicate this finding. 96,97 No other variants in ACE gene have been studied in association with ACE-A.…”
Section: Ace Genementioning
confidence: 99%
“…106 The risk associated with the haplotype is higher compared to the rs3788853 alone (4.9-fold vs 3.0-fold) 95 Moholisa (2013) genotype, in which both copies of the ACE gene lack the 287 base-pair indel region, is associated with higher ACE activity, but not with higher risk of ACEi-A. [96][97][98] One of these studies reported a 50% lower ACE activity in ACEi-A cases compared to controls taking the same drug, and independent of the presence of the insertion/deletion variation 98 and, the two other studies failed to replicate this finding. 109 However, three further case-control studies did not support these initial findings.…”
Section: Ace Genementioning
confidence: 99%
See 2 more Smart Citations
“…Genetic variants associated with ACEi angioedema are typically involved in the activity of or breakdown pathways for bradykinin and substance P. Variants in the bradykinin receptor 2 and neprilysin genes have been implicated as important in patients of African descent . Similarly, variants in the x‐linked X‐prolyl aminopeptidase 2 ( XPNPEP2 ) gene encoding the cytosolic form of aminopeptidase P, a metalloproteinase that degrades bradykinin, has been associated with ACEi angioedema in French Canadians and in both white and black men, but not women, from Tennessee .…”
Section: Reactions Lacking Immunological Memorymentioning
confidence: 99%